2017
DOI: 10.1002/bjs.10328
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of preoperative oral versus intravenous iron in anaemic patients with colorectal cancer

Abstract: Intravenous iron did not reduce the blood transfusion requirement but was more effective than oral iron at treating preoperative anaemia and iron deficiency in patients undergoing colorectal cancer surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
204
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(220 citation statements)
references
References 28 publications
9
204
4
3
Order By: Relevance
“…The results of our study showing the superiority of FCM over oral FeSulf for the treatment and resolution of anaemia secondary to acute GIB is in line with evidence for the efficacy and safety of FCM in a wide range of conditions such as chronic kidney disease, colorectal cancer, inflammatory bowel disease, uterine bleeding and postpartum anaemia . The results are also consistent with a meta‐analysis that assessed studies using different iv iron preparation to treat IDA in patients with different conditions and concluded that although all iv and oral formulations could correct IDA, FCM was the superior treatment …”
Section: Discussionsupporting
confidence: 89%
“…The results of our study showing the superiority of FCM over oral FeSulf for the treatment and resolution of anaemia secondary to acute GIB is in line with evidence for the efficacy and safety of FCM in a wide range of conditions such as chronic kidney disease, colorectal cancer, inflammatory bowel disease, uterine bleeding and postpartum anaemia . The results are also consistent with a meta‐analysis that assessed studies using different iv iron preparation to treat IDA in patients with different conditions and concluded that although all iv and oral formulations could correct IDA, FCM was the superior treatment …”
Section: Discussionsupporting
confidence: 89%
“…It is possible that PIT reduced RBCT by replenishing iron stores, thus, hastening recovery from perioperative blood loss . This is supported by the finding that although intravenous iron was more efficacious in improving preoperative haemoglobin than oral iron supplementation among patients undergoing surgery for colorectal cancer, there was no difference between the groups in terms of patients requiring RBCT or the amounts of red blood cells administered .…”
Section: Discussionmentioning
confidence: 78%
“…Two recent surgical trials involving the use of IV iron to treat pre‐operative anaemia in patients undergoing colorectal and unspecified abdominal surgeries have shown conflicting responses in terms of transfusion outcomes (Froessler et al, ; Keeler et al, ). A trial by Froessler and his colleagues shows a significant reduction in RBC transfusion use by 60% in patients treated with IV iron pre‐operatively (Froessler et al, ).…”
Section: Treatment Strategies For Iron Deficiency Anaemiamentioning
confidence: 99%
“…A systematic review of patients with anaemia undergoing surgery (including orthopaedics, colorectal, gynaecology, spinal, cardiac, upper GI and head and neck) demonstrated an increase in the haemoglobin concentration and reduced to 0·88] with intravenous iron, especially when used with erythropoiesis-stimulating agents (ESAs) or in patients with lower ferritin concentration, without significant difference in mortality or severe adverse events (Lin et al, 2013). Two recent surgical trials involving the use of IV iron to treat pre-operative anaemia in patients undergoing colorectal and unspecified abdominal surgeries have shown conflicting responses in terms of transfusion outcomes (Froessler et al, 2016;Keeler et al, 2017). A trial by Froessler and his colleagues shows a significant reduction in RBC transfusion use by 60% in patients treated with IV iron pre-operatively (Froessler et al, 2016).…”
Section: Pillar 3 Managing Post-operative Anaemiamentioning
confidence: 99%
See 1 more Smart Citation